The Effectiveness of Kinesio Taping Application on the Balance of Recreational Futsal Players - Handoyo, Rudy; Julianti, Hari Peni; Runawang, Khrisna Prasetya Aji (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Futsal is a development of football which is the most popular sport in the world. In futsal there are many demands on individual technical and tactical skills that require a good balance. Kinesio taping stimulate mechanoreceptors, this stimulus can increase proprioception in normal tissue. Proprioception receptors are located in the skin, muscles and joints. For the distal extremities, receptors in the skin and joints become the most important factor. Increasing the ankle proprioception is important to improve balance that supports futsal players. Objective: To determine the effectiveness of kinesio taping on balance, immediately after the application of kinesio taping. Method: This study was a randomized control trial. The subjects were 44 recreational futsal players which were divided into 2 groups, control group (n=22) and treatment group (n=22). The control group performed the mCTSIB test without kinesio tapping application, the treatment group performed the mCTSIB test with kinesio tapping installed. Balance was measured before and after the intervention. Results: The average mCTSIB results in the control group showed an improvement of 1.45±2.59 with p=0.016. The average mCTSIB results in the treatment group showed an improvement of 24.27±1.49 with p=0.000. The results for the difference between pre-test and post-test scores showed a greater increase in the treatment group, this increase was statistically significant, with a value of p=0.000 Conclusion: There is a significant improvement in balance after kinesio taping application. Keywords: Ankle, Balance, Futsal, Kinesio taping, Mechanoreceptors, Proprioception